BABY CRY CLASSIFICATION AND ANALYSIS - Yergesh, Beibit; Zharas, Galymzhan; Uisengali, Dariya; Nurmukhanov, Alisher; Sagatbekov, Dinmukhammed (Nazarbayev University School of Engineering and Digital Sciences, 2024)
We have developed a mobile application that is dedicated to parents and baby carers of newborn babies. The main feature of the app is that it can classify the baby cry sound through use of mobile phones and tell the reason for the baby cry. Moreover, the system includes many good helping features for parents and baby carers such as sleep sounds page, blog page dedicated for care of newborn babies and it maintains the history of cry analysis for every user. Moreover, the system contains a very user friendly design to make it easier to navigate for different group of users inside our mobile application.
Keywords: Research Subject Categories::TECHNOLOGY; Mobile application; Classify a baby's cry; Type of access: Restricted